2015
DOI: 10.1093/jpepsy/jsv002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children With Asthma: A Developmental Perspective

Abstract: Objective The current study investigated whether factors associated with quality of life (QOL) in children with asthma (e.g., family functioning, asthma routines, asthma severity) differed by child age. Methods Participants included 192 children with asthma (5-12 years) and their caregivers. Both children and caregivers completed questionnaires at an initial research session. Family functioning was determined from a mealtime observation that occurred in family homes. Results Child age moderated the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 41 publications
2
36
1
4
Order By: Relevance
“…Since this approach has never been applied to such data, our findings can only partially be compared with previous studies which investigated this relationship marginally. In fact, with regard to asthma severity, some authors have reported significant effects on QoL 21,22 , and an increased risk of behavioural problems when asthma severity increased 1,19,23 . About asthma control, some studies show that uncontrolled status negatively affected only QoL 24,25 , whereas no study has investigated the effect on SDQ.…”
Section: Discussionmentioning
confidence: 99%
“…Since this approach has never been applied to such data, our findings can only partially be compared with previous studies which investigated this relationship marginally. In fact, with regard to asthma severity, some authors have reported significant effects on QoL 21,22 , and an increased risk of behavioural problems when asthma severity increased 1,19,23 . About asthma control, some studies show that uncontrolled status negatively affected only QoL 24,25 , whereas no study has investigated the effect on SDQ.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with well-controlled asthma and lower asthma severity, which lead to a reduction in symptoms and medication use, can have a better quality of life. 11 - 13 The present study is warranted because it is necessary to characterize quality of life in children and adolescents with asthma treated at asthma referral centers. The understanding of the extent to which asthma control status and asthma severity can affect quality of life will help establish therapeutic, environmental, and behavioral strategies, resulting in increased awareness within the health care system as a whole, so that interventions allowing a favorable disease outcome are promoted.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition to cost burden, poor quality of life among asthmatic children has been described in the literature, notably on its effect on school performance, absenteeism, and physical activity participation. 10 A systemic review of 66 studies in 2005, focusing on asthma and school attendance, nearly all showed a correlation between asthma and a proportion of student absenteeism. 11 National and international guidelines emphasize asthma education and preventive measures to minimize exacerbations and maximize control of asthma symptoms in adults and children.…”
mentioning
confidence: 99%